Pengaruh Dana Pihak Ketiga, Non Performing Loan (NPL), Dan Biaya Operasional Pendapatan Operasional (BOPO) Terhadap Penyaluran Kredit Pada Bank Umum Periode 2017-2021 - Gregorius Howok; Ita Sylvia Azita Azis; A. A. Sri Purnami (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2023)
This research aims to analyze the influence of Third Party Funds, Non-Performing Loan, and Operational Cost of Operational Income on credit distribution in commercial banks during the period of 2017-2021. The data used in this research is secondary data obtained from financial reports of commercial banks listed on the Indonesia Stock Exchange during the period of 2017-2021. The analytical method used is multiple linear regression. The results of this research show that Third Party Funds, Non-Performing Loan, and Operational Cost of Operational Income simultaneously have a significant influence on credit distribution. Third Party Funds have a positive and significant influence on credit distribution. Non-Performing Loan has a positive and significant influence on credit distribution. Operational Cost of Operational Income has a negative and significant influence on credit distribution.